Prediction of the Variation of Swelling Pressure and 1-D Heave of Expansive Soils with respect to Suction - Tu, Hongyu (Université d'Ottawa / University of Ottawa, 2015)
The one-dimensional (1-D) potential heave (or swell strain) of expansive soil is conventionally estimated using the swelling pressure and swelling index values which are determined from different types of oedometer test results. The swelling pressure of expansive soils is typically measured at saturated condition from oedometer tests. The experimental procedures of oedometer tests are cumbersome as well as time-consuming for use in conventional geotechnical engineering practice and are not capable for estimating heave under different stages of unsaturated conditions. To alleviate these limitations, semi-empirical models are proposed in this thesis to predict the variation of swelling pressure of both compacted and natural expansive soils with respect to soil suction using the soil-water characteristic curve (SWCC) as a tool. An empirical relationship is also suggested for estimating the swelling index from plasticity index values, alleviating the need for conducting oedometer tests. The predicted swelling pressure and estimated swelling index are then used to estimate the variation of 1-D heave with respect to suction for expansive soils by modifying Fredlund (1983) equation. The proposed approach is validated on six different compacted expansive soils from US, and on eight field sites from six countries; namely, Saudi Arabia, Australia, Canada, China, US, and the UK. The proposed simple techniques presented in this thesis are friendly for the practitioners for using when estimating the heave in unsaturated expansive soils.
Keywords: Expansive soil; Swelling pressure; Ground Heave; Soil suction; Soil-water characteristic curve